Animal glue composite hydrogel as well as preparation method and application thereof

Through the preparation of animal glue composite hydrogel, the problem that existing materials are difficult to take into account the mechanical properties of the intervertebral disc is solved, and the mechanical properties and tissue adhesion similar to the natural nucleus pulposus are achieved, and the nucleus pulposus repair is promoted.

CN119656392APending Publication Date: 2025-03-21ZHUHAI NAJIN HEALTH TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510054848.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

While existing materials meet the biomechanical, composition, structural and functional conditions of the intervertebral disc, it is difficult to take into account the mechanical properties of the intervertebral disc, resulting in the inability of the materials to provide effective mechanical assistance and high support, and cannot adapt to the mechanical environment for nucleus pulposus repair.

Method used

Animal gel composite hydrogel is used to mix animal gel, polyvinyl alcohol, glycerin and water in a specific mass ratio to form an injectable gel, which has rheological and mechanical properties similar to the natural nucleus pulposus, adapts to the mechanical environment of the intervertebral disc, and has tissue adhesion to avoid leakage.

Benefits of technology

It achieves mechanical properties similar to the natural nucleus pulposus, is suitable for the mechanical environment of the intervertebral disc, has tissue adhesion, avoids leakage, and inhibits lipid peroxidation of nucleus pulposus cells in reactive oxygen species, and promotes nucleus pulposus repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656392A_ABST
    Figure CN119656392A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogel, and particularly relates to animal glue composite hydrogel as well as a preparation method and application thereof. The animal glue composite hydrogel comprises animal glue, polyvinyl alcohol, glycerol and water. The animal glue composite hydrogel provided by the invention not only has rheological and mechanical properties similar to those of natural nucleus pulposus, adapts to the mechanical environment of intervertebral discs, but also has tissue adhesion, can be adhered to soft tissues and avoid leakage, and also can inhibit lipid peroxidation of nucleus pulposus cells in the reactive oxygen species (ROS) environment, reduce cell ferroptosis and promote nucleus pulposus repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical hydrogels, and in particular relates to an animal glue composite hydrogel and a preparation method and application thereof. Background Art

[0002] Low back pain (LBP) is a very common physical disease that seriously affects the patient's quality of life. Low back pain is also the second leading cause of hospitalization and the main cause of disability worldwide. With the acceleration of population aging, the incidence of degenerative spinal diseases has increased significantly, and the number of patients with low back pain has also increased year by year, bringing a serious economic burden to patients' families and society. Intervertebral disc degeneration is one of the main causes of low back pain. The degeneration of the nucleus pulposus, annulus fibrosus and cartilage endplate of the intervertebral disc caused by aging, excessive activity and overload will cause low back pain, which will gradually worsen and further lead to movement disorders.

[0003] Studies have shown that hydrogels composed of hydrophilic polymers provide a new option for the repair and regeneration of the nucleus pulposus due to their bioactivity and biodegradability. However, due to the specificity of the intervertebral disc's own biomechanics, composition, structure and function, the various materials currently reported are difficult to take into account the mechanical properties of the intervertebral disc while meeting the above conditions, resulting in the material itself being unable to provide effective mechanical assistance and high support for the intervertebral disc, and unable to provide a mechanical environment suitable for nucleus pulposus repair.

[0004] Polyvinyl alcohol (PVA) is a synthetic polymer material with biocompatibility. Glycerol contains a large number of hydroxyl groups, which can form multiple hydrogen bonds with PVA and act as a bridge molecule to connect PVA chains into a three-dimensional network structure, thereby further improving the mechanical strength and stable three-dimensional network structure of the hydrogel. The composite hydrogel of glycerol and PVA has been reported to be used for filling and repairing the nucleus pulposus. Through the water retention of glycerol and the mechanical properties of the hydrogel close to the nucleus pulposus, a certain nucleus pulposus repair effect has been achieved without adding any active ingredients. However, it is difficult for this material to form a stable interface with the nucleus pulposus tissue. During weight-bearing and exercise, the hydrogel may be squeezed and flow out through the damaged annulus fibrosus.

[0005] Collagen-based animal glue is widely used as an adhesive, binder and solidifying agent for organic and inorganic materials. There are various types of animal glue on the market, such as hide and bone glue, fish bladder glue, tortoise shell glue and gelatin. Animal glue is a natural polymer extracted from collagen of mammals or fish. Its aqueous solution has surface activity and high viscosity. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide an animal glue composite hydrogel and its preparation method and application. The animal glue composite hydrogel not only has rheological and mechanical properties similar to those of natural nucleus pulposus and adapts to the mechanical environment of the intervertebral disc, but also has tissue adhesion and can adhere to soft tissue to avoid leakage.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The invention provides an animal glue composite hydrogel, comprising: animal glue, polyvinyl alcohol, glycerol and water; the mass ratio of the animal glue, polyvinyl alcohol, glycerol and water is 0.1-1.5:0.1-0.3:3-8:2-8.

[0009] Preferably, the animal glue is animal-derived gelatin; the animal-derived gelatin includes one or more of fish bladder glue, fish skin glue, cowhide glue and donkey skin glue; the weight average molecular weight of the polyvinyl alcohol is 1500-220000.

[0010] The present invention also provides a method for preparing the animal glue composite hydrogel described in the above technical solution, comprising the following steps: mixing an aqueous solution of animal glue, an aqueous solution of polyvinyl alcohol and glycerol, and allowing the obtained viscous solution to stand and solidify to obtain the animal glue composite hydrogel.

[0011] Preferably, the mass concentration of the animal glue in the aqueous solution of animal glue is 15-40%.

[0012] Preferably, the mass concentration of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 5-15%.

[0013] Preferably, the mixing temperature is 45-65°C.

[0014] Preferably, the mixing is performed under stirring conditions; the stirring rate is 10 to 500 rpm.

[0015] Preferably, the static curing time is 3 to 6 hours; the static curing is carried out at room temperature; and the room temperature is 15 to 42°C.

[0016] Preferably, the method for preparing the aqueous solution of animal glue comprises the following steps: soaking the animal glue in water, dissolving it in a water bath and eliminating bubbles in sequence to obtain the aqueous solution of animal glue; the soaking time is 12 to 24 hours; the temperature of the water bath dissolution is 45 to 65°C.

[0017] The present invention also provides the use of the animal glue composite hydrogel described in the above technical solution or the animal glue composite hydrogel prepared by the preparation method described in the above technical solution in the preparation of nucleus pulposus repair preparations.

[0018] The present invention provides an animal glue composite hydrogel, comprising: animal glue, polyvinyl alcohol, glycerol and water; the mass ratio of the animal glue, polyvinyl alcohol, glycerol and water is 0.1-1.5:0.1-0.3:3-8:2-8. In the animal glue composite hydrogel provided by the present invention, polyvinyl alcohol (PVA) has biocompatibility, and glycerol contains a large number of hydroxyl groups, which can form multiple hydrogen bonds with PVA, and act as a bridge molecule to connect the PVA chains into a three-dimensional network structure to form an injectable gel. Animal glue contains components such as elastin and glycosaminoglycans, and has a high viscosity, which increases the viscosity, density and mechanical strength of the hydrogel, and its aqueous solution has surface activity, and will freeze into an elastic gel after cooling, which can play a certain mechanical support role. Therefore, the animal glue composite hydrogel not only has rheological and mechanical properties similar to those of natural nucleus pulposus and adapts to the mechanical environment of the intervertebral disc, but also has tissue adhesion and can adhere to soft tissue (annulus fibrosus) to avoid leakage. It can also inhibit the occurrence of lipid peroxidation of nucleus pulposus cells in the reactive oxygen species (ROS) environment, reduce cell ferroptosis, and promote nucleus pulposus repair. It has great potential in the preparation of drugs for the treatment of intervertebral disc degeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the preparation method of the aqueous solution of animal glue (NG) and the composite hydrogel of animal glue (GPG-NG) in the embodiment of the present invention;

[0020] Figure 2 It is a comparison diagram of the aqueous solution of animal glue (NG) in Example 1, the composite hydrogel of animal glue (GPG-NG) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1 before curing (top) and after curing (bottom);

[0021] Figure 3 It is a solidification time diagram of the aqueous solution of animal glue (NG) in Example 1, the composite hydrogel of animal glue (GPG-NG) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1;

[0022] Figure 4 The adhesion test diagram (a), the adhesion diagram of the hydrogel and the annular fibrosis tissue (b), and the extrusion test diagram (c) of the aqueous solution of animal glue in Example 1 (NG), the composite hydrogel of animal glue (GPG-NG) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1;

[0023] Figure 5 The infrared spectra of the aqueous solution of animal glue (NG) in Example 1, the composite hydrogel of animal glue (GPG-NG) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1;

[0024] Figure 6The graph is a graph showing the relationship between the storage modulus (G′), the loss modulus (G″) and the loss factor (G″ / G′) of the composite hydrogel (a) in Comparative Example 1 and the animal glue composite hydrogel (b) in Example 2 as a function of frequency;

[0025] Figure 7 The graph is a graph showing the relationship between the storage modulus (G′), loss modulus (G″) and loss factor (G″ / G′) of the animal glue composite hydrogel in Example 3 and the frequency;

[0026] Figure 8 The graph is a graph showing the relationship between the storage modulus (G′), loss modulus (G″) and loss factor (G″ / G′) of the animal glue composite hydrogel in Example 4(d) and Example 5(e) as a function of frequency;

[0027] Fig. 9 The hydrogel stress-strain curve diagram (g) of the composite hydrogel in comparative example 1 and the animal glue composite hydrogel in Example 2 and the cyclic compression loading-unloading curve diagram (h) of the animal glue composite hydrogel (GPG9-NG1) in Example 2 and the composite hydrogel (GPG) in comparative example 1;

[0028] Fig.10 The stress-strain curves of the animal glue composite hydrogel (GPG9-NG1) in Example 2 and the composite hydrogel (GPG) in Comparative Example 1;

[0029] Fig.11 The hydrogel injection force-displacement curve diagram (a) of the animal glue composite hydrogel (GPG9-NG1) in Example 2 and the composite hydrogel (GPG) in Comparative Example 1 and the dynamic sliding force (DGF) diagram (b) of the uncured hydrogel during injection;

[0030] Fig.12 The contact angle data graph (c) and swelling graph (d) of the aqueous solution of animal glue in Example 1 (NG), the composite hydrogel of animal glue (GPG9-NG1) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1;

[0031] Fig.13 The water retention rate graph (e) and the degradability graph (f) of the aqueous solution of animal glue (NG) in Example 1, the composite hydrogel (GPG9-NG1) of animal glue in Example 2, and the composite hydrogel (GPG) in Comparative Example 1;

[0032] Fig.14 The initial state diagram (g) and the state diagram (h) of the aqueous solution of animal glue in Example 1 (NG) and the composite hydrogel of animal glue (GPG9-NG1) in Example 2 after degradation at 37°C for 2 hours;

[0033] Fig.15It is the LPO staining image of the composite hydrogel (GPG) in Comparative Example 1 and the animal glue composite hydrogel (GPG9-NG1) in Example 2;

[0034] Fig.16 It is the LPO fluorescence intensity diagram of the composite hydrogel (GPG) in Comparative Example 1 and the animal glue composite hydrogel (GPG9-NG1) in Example 2;

[0035] Fig.17 The CCK-8 graphs of the extracts of the composite hydrogel (GPG) in Comparative Example 1 and the composite hydrogel (GPG-NG) in Example 2 and NPCs cells after 1 and 3 days of culture;

[0036] Fig.18 Live / Dead staining images of the extract of the composite hydrogel (GPG) in Comparative Example 1 and the composite hydrogel (GPG-NG) of animal glue in Example 2 after culturing with NPCs cells for 1 day;

[0037] Fig.19 The composite hydrogel (GPG) in comparative example 1 and the composite hydrogel (GPG9-NG1) in example 2 are ROS staining images of cells under hydrogen peroxide stimulation (a) and MMP13 immunofluorescence staining images of cells under hydrogen peroxide stimulation (b);

[0038] Fig. 20 The composite hydrogel (GPG) in Comparative Example 1 and the animal glue composite hydrogel (GPG9-NG1) in Example 2 were subjected to macrophage IL-10 immunofluorescence staining under LPS stimulation;

[0039] Fig.21 The composite hydrogel (GPG) in Comparative Example 1 and the composite hydrogel (GPG9-NG1) in Example 2 were subjected to macrophage TNF-α immunofluorescence staining under LPS stimulation;

[0040] Fig. 22 Pathological sections of various tissues of rats after material implantation, including (a) four weeks and (b) eight weeks;

[0041] Fig.23 MRI images of rats 8 weeks after surgery (a) and H&E staining and Safranin-O / fast green staining images of the coccygeal intervertebral discs of rats in various treatment groups at 8 weeks, respectively (b), where the upper image is the H&E staining image and the lower image is the Safranin-O / fast green staining image. DETAILED DESCRIPTION

[0042] The invention provides an animal glue composite hydrogel comprising: animal glue, polyvinyl alcohol, glycerol and water; the mass ratio of the animal glue, polyvinyl alcohol, glycerol and water is 0.1-1.5:0.1-0.3:3-8:2-8.

[0043] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.

[0044] As an embodiment, the mass ratio of the animal glue, polyvinyl alcohol, glycerol and water is 0.1-1.5:0.1-0.3:3-8:2-8, as another embodiment, it is 0.5-1:0.15-0.25:5-8:4-7, and in a specific embodiment, it is 0.5:0.23:6.8:4.6.

[0045] As the amount of PVA and animal glue increases, the mechanical properties of the hydrogel increase, and the gel hardness should be similar to that of a healthy nucleus pulposus. Hydrogels that are too hard increase the risk of adversely affecting load transfer. Softer hydrogels are more likely to disperse and leach out of the annulus and fail to fully restore mechanical properties.

[0046] As an embodiment, the animal glue is animal-derived gelatin; the animal-derived gelatin includes one or more of fish bladder glue, fish skin glue, cowhide glue and donkey skin glue; the weight average molecular weight of the polyvinyl alcohol is 1500-220000.

[0047] As an embodiment, the weight average molecular weight of the polyvinyl alcohol is 1500 to 220000, and in a specific embodiment, it is 1750 to 10000. Polyvinyl alcohols of different molecular weights will affect the amount of animal glue used and the gelling effect.

[0048] As an embodiment, the storage modulus of the animal glue composite hydrogel is 200Pa-1400Pa, 244Pa, 556Pa, 1010Pa or 1370Pa in a specific embodiment, the surface water contact angle is 10-30°, 15.2±2.97° in a specific embodiment, the swelling rate is 10-20%, 14.9±3.1% in a specific embodiment, the water retention rate is 60-85%, 78.4% in a specific embodiment,

[0049] The present invention compounds animal glue into polyvinyl alcohol-glycerol hydrogel to improve the viscosity and elasticity of the hydrogel and enhance its nucleus pulposus repair effect. Glycerol molecules can form multiple hydrogen bonds with PVA and animal glue to generate a hydrogel network. Animal glue itself is a natural viscous material, which can provide viscosity for the hydrogel, and has extremely high density after cross-linking to enhance the mechanical strength of the animal glue composite hydrogel. After the animal glue composite hydrogel is injected into the intervertebral disc, the animal glue composite hydrogel shows good adhesion to the tissue, stays in the intervertebral disc, and begins to gel in situ. Due to the cross-linked network formed between glycerol, PVA and animal glue, the animal glue composite hydrogel shows structural stability and can play a certain mechanical support. Many studies have shown that under the stimulation of inflammatory factors, nucleus pulposus cells will undergo apoptosis, thereby causing their extracellular matrix, and the mechanical properties of nucleus pulposus tissue will change, thereby causing intervertebral disc (IVD) degeneration. In the intervertebral disc tissue, matrix metalloproteinase 13 (MMP13) can specifically degrade type II collagen (COL-II), the main component of the intervertebral disc extracellular matrix (ECM), and the imbalance between the production and degradation of ECM is the main cause of intervertebral disc degeneration. Therefore, blocking the oxidative stress process through biomaterials, further inhibiting the activation of acid-sensitive channels and the occurrence of downstream inflammatory cascade reactions, and promoting the reconstruction of the extracellular matrix are important treatment options for IVD. Animal glue contains bioactive molecules such as amino acids, glycosaminoglycans, gelatin, and collagen, which have the effects of scavenging free radicals and anti-oxidation, reducing the production of reactive oxygen species, inhibiting lipid peroxidation in the body, improving the oxidative stress microenvironment in the body, promoting the synthesis of COL-II, inhibiting the secretion of matrix metalloproteinase (MMP13), and promoting the regeneration of ECM; in addition, it promotes the production of anti-inflammatory factor interleukin 10 (IL-10), inhibits the production of pro-inflammatory factors, and alleviates the inflammatory environment in the body, thereby promoting nucleus pulposus repair.

[0050] The animal glue composite hydrogel provided by the present invention is injectable, can be injected in a minimally invasive manner and can self-gel in situ without the need for any additional chemical cross-linking agents or physical cross-linking methods.

[0051] The present invention also provides a method for preparing the animal glue composite hydrogel described in the above technical solution, comprising the following steps: mixing an aqueous solution of animal glue, an aqueous solution of polyvinyl alcohol and glycerol, and allowing the obtained viscous solution to stand and solidify to obtain the animal glue composite hydrogel.

[0052] As an embodiment, the mass concentration of the animal glue in the aqueous solution of the animal glue is 15-40%, and in a specific embodiment, it is 30-35%.

[0053] As an embodiment, the method for preparing the aqueous solution of animal glue comprises the following steps: soaking the animal glue in water, dissolving it in a water bath and eliminating bubbles in sequence to obtain the aqueous solution of animal glue.

[0054] As an implementation mode, the water is deionized water; the soaking time is 12 to 24 hours, and in a specific embodiment, it is 20 to 24 hours.

[0055] As an embodiment, the temperature of the water bath dissolution is 45 to 65°C, and in a specific embodiment, it is 50 to 65°C; the water bath dissolution is carried out under stirring; the stirring rate is 50 to 150 rpm, and in a specific embodiment, it is 100 to 120 rpm; the present invention has no special limitation on the time of the water bath dissolution, until the glue is completely dissolved.

[0056] As an embodiment, the method for eliminating bubbles is ultrasound; the ultrasound time is 5 to 30 minutes, and in a specific embodiment, it is 10 to 20 minutes; the ultrasound power is 60 to 80W, and in a specific embodiment, it is 70W. Bubbles make the aqueous solution of animal glue uneven, and bubbles will cause inaccurate volume measurement when adding solution later. The present invention eliminates bubbles generated during the stirring process of water bath dissolution through ultrasound to obtain a homogeneous and clear aqueous solution of animal glue.

[0057] As an embodiment, the mass concentration of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol (PVA) is 5-15%, and in a specific embodiment, it is 6-10%. As an embodiment, the preparation method of the aqueous solution of polyvinyl alcohol comprises the following steps: dissolving polyvinyl alcohol in water to obtain the aqueous solution of polyvinyl alcohol; the water is deionized water; the dissolution temperature is 95-100°C, and in a specific embodiment, it is 95°C; the dissolution is carried out under stirring; the stirring speed is 100-150rpm, and in a specific embodiment, it is 110-120rpm. The present invention does not specifically limit the stirring time, and stirring until complete dissolution is sufficient.

[0058] As an embodiment, the volume ratio of the aqueous solution of animal glue, glycerol and polyvinyl alcohol is 0.1-0.9:1.2-1.7:1, and in a specific embodiment, it is 0.25-0.85:1.5:1.

[0059] As an embodiment, the mixing is: adding the aqueous solution of glycerol and animal glue to the aqueous solution of polyvinyl alcohol in sequence; the mixing temperature is 45 to 65°C, and in a specific embodiment, it is 50 to 65°C; the mixing is carried out under stirring; the stirring speed is 50 to 150 rpm, and in a specific embodiment, it is 100 rpm. The present invention has no special limitation on the stirring time, and the raw materials can be stirred evenly.

[0060] PVA needs to be heated to 95℃ to dissolve, while animal glue needs 65℃. If the temperature is too high, the animal glue components will be inactivated, so prepare the PVA aqueous solution first and then add other raw materials.

[0061] As an embodiment, the static curing time is 3 to 6 hours, and in a specific embodiment, it is 4 to 5 hours. The static curing is carried out at room temperature; the room temperature is 25 to 37° C., and in a specific embodiment, it is 30 to 37° C.

[0062] As an embodiment, before the static curing, the method further comprises: placing the obtained viscous solution in a mold; the present invention has no special limitation on the mold, and any mold well known in the art can be used.

[0063] Figure 1 Schematic diagram of the preparation method of the aqueous solution of animal glue (NG) and the composite hydrogel of animal glue (GPG-NG) in the embodiment of the present invention. Figure 1 As shown, the present invention mixes animal glue and deionized water, heats, and cools to obtain an aqueous solution of animal glue (NG), which contains collagen, other proteins, sugars, and amino acids; adds animal glue and glycerol to polyvinyl alcohol, heats and stirs, and solidifies at room temperature to obtain an animal glue composite hydrogel.

[0064] The present invention also provides the use of the animal glue composite hydrogel described in the above technical solution or the animal glue composite hydrogel prepared by the preparation method described in the above technical solution in the preparation of nucleus pulposus repair preparations.

[0065] As an embodiment, the nucleus pulposus repair preparation is an injectable preparation.

[0066] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0067] Example 1

[0068] Preparation of an aqueous solution of animal glue: Weigh animal glue (fish bladder glue) and deionized water in a mass ratio of 1:2, soak the animal glue in deionized water for 24 hours, then stir evenly at 100 rpm in a 65°C water bath to completely dissolve it, and ultrasonicate it in an ultrasonic cleaner at 70 W for 5 minutes to eliminate the bubbles generated during the stirring process, and obtain a homogeneous and clear 33.3 wt% aqueous solution of animal glue, which is named NG.

[0069] Example 2

[0070] Preparation of animal glue composite hydrogel: 1.2 g PVA was dissolved in 18.8 mL deionized water, stirred at 95 ° C and 110 rpm until completely dissolved to obtain a 6 wt% PVA aqueous solution, and then 28.2 mL glycerol was added to the PVA aqueous solution and stirred evenly at 95 ° C and 100 rpm to obtain a PVA / glycerol solution. The animal glue aqueous solution of Example 1 was added to the PVA / glycerol solution, and the volume of the animal glue aqueous solution accounted for 10% of the volume of the PVA / glycerol solution. Stir at 65 ° C and 100 rpm to obtain a uniform viscous solution. The viscous solution was transferred to a mold and allowed to stand and cure at room temperature 37 ° C for 4 hours to obtain an animal glue composite hydrogel, which was recorded as GPG9-NG1.

[0071] Example 3

[0072] The difference from Example 2 is that the volume of the aqueous solution of animal glue is 15% of the volume of the PVA / glycerol solution, and the rest of the contents are the same as Example 2, to obtain an animal glue composite hydrogel, which is recorded as GPG8.5-NG1.5.

[0073] Example 4

[0074] The difference from Example 2 is that the volume of the aqueous solution of animal glue is 20% of the volume of the PVA / glycerol solution, and the rest of the contents are the same as Example 2, to obtain an animal glue composite hydrogel, which is recorded as GPG8-NG2.

[0075] Example 5

[0076] The difference from Example 2 is that the volume of the aqueous solution of animal glue is 25% of the volume of the PVA / glycerol solution, and the rest of the contents are the same as Example 2, to obtain an animal glue composite hydrogel, which is recorded as GPG7.5-NG2.5.

[0077] Comparative Example 1

[0078] The difference from Example 2 is that no aqueous solution of animal glue is added. The rest of the contents are the same as Example 2, and a composite hydrogel is obtained, which is recorded as GPG or GPG-NG 10-0.

[0079] Performance Testing

[0080] (1) In vitro curing time test

[0081] The uncured aqueous solution of animal glue in Example 1 (NG), the composite hydrogel of animal glue in Example 2 (GPG-NG), and the composite hydrogel in Comparative Example 1 (GPG) were placed in a transparent weighing bottle, and the weighing bottle was shaken to observe the state changes. The results are as follows: Figure 2 As shown, the time it takes for the hydrogel to change from a transparent solution to a gel-like solid is recorded. The results are shown in Figure 3 shown.

[0082] from Figure 2 and 3 It can be seen that the composite hydrogels are transparent solutions before solidification and have high fluidity. The gel curing time of GPG is 4.1±0.19h, and the gel curing time of NG is 0.47±0.06h. Due to the presence of animal glue, the gel curing time of GPG-NG is extended to 4.3±0.1h.

[0083] (2) Viscosity test

[0084] The hydrogel was made into a cylinder with a diameter of 12mm and a height of 2mm. The surface was lightly touched to observe the adhesion of the hydrogel. In addition, in order to study the actual situation of the material in the intervertebral disc, an in vitro model was established to verify the viscosity of the material in vivo. Excess tissue was removed from the fresh sheep spine, and the upper and lower vertebrae were laterally separated from the intervertebral disc to expose the cross-section of the intervertebral disc annulus fibrosus. The nucleus pulposus tissue was removed, and equal amounts of uncured GPG, NG, and GPG-NG were injected into the central position of the intervertebral disc, and the spine was tilted to observe the adhesion of the hydrogel. In addition, fresh sheep spines were taken, excess tissue was removed, and the intact intervertebral disc and upper and lower vertebrae were retained. The hydrogel was injected into the nucleus pulposus position, and a 12N load was applied to the vertebral body to observe the leakage of the hydrogel.

[0085] The adhesion test results of the animal glue aqueous solution (NG) in Example 1, the animal glue composite hydrogel (GPG-NG) in Example 2 and the composite hydrogel (GPG) in Comparative Example 1 after gel curing are as follows: Figure 4 As shown in a, GPG gel is non-sticky and does not adhere to the surface after light touch; NG gel is more sticky and can lift the culture dish off the table to a certain height, while GPG-NG gel is more sticky than GPG and can lift the culture dish off the table.

[0086] The adhesiveness of the aqueous solution of animal glue (NG) in Example 1 and the composite hydrogel of animal glue (GPG-NG) in Example 2 to the annulus fibrosus tissue is as follows: Figure 4 As shown in (b), the GPG gel flows out from the edge (black circle part), the NG gel solidifies in the annulus fibrosus part and adheres to it, and the GPG-NG gel adheres to the annulus fibrosus tissue without flowing out.

[0087] The gel leakage of the animal glue composite hydrogel (GPG-NG) in Example 2 and the composite hydrogel (GPG) in Comparative Example 1 is as follows: Figure 4 As shown in c, GPG gel flows out from the injection hole, while GPG-NG gel does not flow out.

[0088] (3) FTIR analysis

[0089] The Fourier transform attenuated total reflection infrared spectrum of the sample was measured by infrared spectrometer to analyze the main functional groups in the hydrogel sample, with a scanning range of 500-4000cm -1 , scanning accuracy 4cm -1 .

[0090] The Fourier transform infrared spectra of the aqueous solution of animal glue (NG) in Example 1, the composite hydrogel of animal glue (GPG-NG) in Example 2, and the composite hydrogel (GPG) in Comparative Example 1 are as follows: Figure 5 As shown in the figure, OH and CO in GPG gel are at 3290 cm -1 and 1040cm -1 NG at 1250cm -1 , 1460cm -1 , 1550cm -1 , 1650cm -1 , 3280cm -1 Obvious peaks can be observed at 1250cm -1 (amide III), 1550 cm -1 (amide II), 1650 cm -1 (Amide I) The substances corresponding to these peaks are mainly amides. In addition to the OH and CO bonds at 3290 and 1040, GPG-NG also shows 1550cm -1 、1650cm -1 The presence of amide I and amide II bonds indicated that the hydrogel contained animal glue components.

[0091] (4) Mechanical properties

[0092] Rheological testing: The rheological properties of the organohydrogel were tested using an advanced rotational rheometer. The samples were prepared into square sheets with a diameter of 10 mm and a height of 1 mm. A flat plate fixture with a diameter of 20 mm was used to test the storage modulus, energy dissipation modulus and loss factor of the samples at 0.1-10 Hz at 37°C and 1% strain.

[0093] The viscoelastic properties of the hydrogels were characterized using a rotational rheometer. Figure 6 The graph is a graph showing the relationship between the storage modulus (G′), the loss modulus (G″) and the loss factor (G″ / G′) of the composite hydrogel (a) in Comparative Example 1 and the animal glue composite hydrogel (b) in Example 2 as a function of frequency; Figure 7 The graph is a graph showing the relationship between the storage modulus (G′), loss modulus (G″) and loss factor (G″ / G′) of the animal glue composite hydrogel in Example 3 and the frequency;

[0094] Figure 8Graph showing the relationship between the storage modulus (G′), loss modulus (G″) and loss factor (G″ / G′) of the animal glue composite hydrogel in Example 4(d) and Example 5(e) as a function of frequency.

[0095] Figures 6 to 8 The results show that the storage modulus (G') of the hydrogel scaffolds is higher than the energy loss modulus (G"), indicating that the hydrogels are in a viscoelastic solid state. At the same time, when the oscillation frequency is 1 Hz, the storage moduli of the GPG, GPG9-NG1, GPG8.5-NG1.5, GPG8-NG2, and GPG7.5-NG2.5 groups are approximately 190Pa, 244Pa, 556Pa, 1010Pa, and 1370Pa, respectively, indicating that as the content of animal glue in the hydrogel increases, the stiffness of the hydrogel scaffold also increases accordingly. The storage modulus of the natural nucleus pulposus from pigs is about 307Pa, and the storage moduli of GPG9-NG1 and GPG8.5-NG1.5 are closer, which can be further studied.

[0096] Dynamic compression test: This test uses a mechanical testing machine to perform a cyclic compression test on the gel sample at a speed of 10mm / min. The gel sample is compressed to a constant compression strain of 30%, and then the load is unloaded to 0. Static compression test: The gel sample is compressed until it breaks. The compression modulus of each sample is determined by the slope of the stress-strain curve at a strain of 10%. The mechanical properties experiment was repeated 3 times with different samples. The hydrogel was mechanically tested using a universal mechanical testing machine at a compression strain of 30%. Fig. 9 It is the hydrogel stress-strain curve diagram of the composite hydrogel in comparative example 1 and the animal glue composite hydrogel in Examples 2 to 5 (g) and the cyclic compression loading-unloading curve diagram of the animal glue composite hydrogel (GPG9-NG1) in Example 2 and the composite hydrogel (GPG) in comparative example 1 (h).

[0097] from Fig. 9 It can be seen from the figure that as the glue content of animal glue increases, the mechanical strength of the hydrogel also increases. The results of multiple cycles of compression show that the hydrogel has good elasticity ( Fig. 9 h), but the gel hardness should be similar to that of a healthy nucleus pulposus. Hydrogels that are too hard increase the risk of adversely affecting load transfer. Softer hydrogels are more likely to disperse and leach out of the annulus and fail to fully restore mechanical properties. In summary, GPG-NG concentrations of GPG9-NG1 were selected for subsequent experiments. Fig.10 The stress-strain curves of the composite hydrogel (GPG9-NG1) of Example 2 and the composite hydrogel (GPG) of Comparative Example 1 are shown in FIG. Fig.10It can be seen that the GPG gel breaks at about 62% strain, while the GPG9-NG1 gel breaks at about 78% strain, indicating that the GPG9-NG1 gel can withstand a larger load and has better mechanical properties.

[0098] (5) Injection performance test

[0099] In order to quantify the injectability of the hydrogel, the dynamic sliding force (DGF) of uncured GPG and GPG9-NG1 during injection was measured with reference to the reported method (DGF is the force required to support the movement of the plunger to discharge the substance in the syringe, i.e., the push force). The uncured hydrogel GPG and GPG9-NG1 solution was placed in a 10mL syringe with a 22G needle and fixed on a universal mechanical testing machine with a bracket so that the plunger end of the syringe was in close contact with the mechanical loading unit. In the compression mode, the loading unit was driven at a compression rate of 10mm / min to simulate the manual injection process, the injection force during the injection process was recorded, and the size of the DGF was measured to evaluate the injectability of the sample. Each sample was tested three times, and the average DGF was fitted.

[0100] The results of injection force of GPG and GPG9-NG1 are as follows Fig.11 As shown in a and b, the DGF when injected through a 10mL syringe with a 22G needle is approximately 10.37±0.37N and 25.28±2.85, respectively, which indicates that the presence of animal glue also increases the push force of the injectable hydrogel scaffold when it is not solidified, and the animal glue increases the viscosity of the hydrogel. The push force of an average adult with one hand is about 50N, indicating that the hydrogel is easy to push out of the syringe when it is not solidified, and can be used for intervertebral disc puncture injection with an extremely fine needle.

[0101] (6) Wettability test

[0102] The wettability of the hydrogel was examined by contact angle measurement. Fig.12 As shown in Figure c, the water contact angle of the GPG9-NG1 surface (15.2±2.97°) is significantly lower than that of pure NG (41.57±1.99°) and also lower than that of GPG (27.27±6.02°), indicating that the hydrophilicity of GPG9-NG1 is higher than that of pure NG and GPG.

[0103] (7) Swelling capacity test

[0104] The relationship curve between the swelling capacity and time of the hydrogel sample is obtained by measuring the free absorption capacity at continuous time intervals. The initial mass of the wet gel is Wd. The gel is soaked at room temperature and weighed every 60 minutes until the mass at swelling equilibrium is Ws. The equilibrium swelling ratio SR is: SR = (Ws-Wd) / Wd×100%. The swelling results are shown in Fig.12 As shown in middle d, the swelling rate was measured under wet weight conditions, and the swelling rates of GPG and GPG9-NG1 were relatively low at around 11.5±0.1% and 14.9±3.1%, while the swelling rate of NG gel was around 126±18.7%. Excessive swelling of the hydrogel used for the intervertebral disc will cause damage to it.

[0105] (8) Water retention performance test

[0106] The water retention properties of the hydrogels were tested using methods reported in the references. The specific test method is as follows: cylindrical GPG, NG and GPG9-NG1 hydrogels were placed in a constant temperature and humidity chamber at 37°C and 50% relative humidity. An electronic analytical balance was used to measure the initial weight (W0) of the sample and the weight (Wt) at different time points in the constant temperature and humidity chamber. The mass retention rate of the sample was calculated according to the formula to evaluate its water retention capacity: water retention capacity = Wt / W0 × 100%. The water retention performance test results show that ( Fig.13 In figure e), the water retention rate of GPG and GPG9-NG1 gels was still about 80% after being placed at 37°C and 50% relative humidity for 14 days. After the NG gel was exposed to the external environment, its mass decreased to 34.2% of the initial mass due to water loss, while the mass of GPG9-NG1 gel decreased to 78.4% of the initial mass, indicating that the water retention performance of GPG9-NG1 gel was better.

[0107] (9) Degradability test

[0108] In order to study the biodegradability of the hydrogel, the hydrogel was weighed and the initial weight (W0) was recorded. The hydrogel was placed in a sealed tube containing PBS (pH = 7.4) at 37°C to simulate physiological conditions. After that, the hydrogel was weighed regularly, the mass of the hydrogel was weighed after wiping the surface water with filter paper, and finally, the biodegradation rate of the hydrogel was calculated based on the remaining weight of the hydrogel. The hydrogel was weighed once a day (Wt). The biodegradation rate was determined by the equation Wt / W0.

[0109] The hydrogel material was immersed in PBS to test its in vitro degradation performance. Fig.13 As shown in Figure f, after 14 days in PBS, the weight loss of GPG was 35%, while the weight loss of GPG9-NG1 gel was 21.6%. The reason why GPG9-NG1 lost less mass may be that the new bonds formed by animal glue and PVA and glycerol are stronger than the binding force of simple PVA and glycerol. In addition, the viscosity of animal glue itself makes GPG9-NG1 gel more tightly bound and has less mass loss.

[0110] Fig.14g and h are the comparison of the degradation of GPG9-NG1 and NG. Fig.14 As shown in g, after being placed in a 37°C environment for 2 hours, the results are as follows Fig.14 As shown in middle h, NG was dissolved in phosphate buffered saline (PBS), the color of the solvent changed to yellow, while GPG9-NG1 still maintained its original shape. Compared with NG, GPG9-NG1 gel can effectively preserve the animal glue component.

[0111] (10) In vitro cell experiments on hydrogels

[0112] 1. Cytocompatibility

[0113] Referring to ISO 10993-5, the cell compatibility of GPG9-NG1 was evaluated by culturing rat nucleus pulposus (NPCs) for 1 day and 3 days using an organic hydrogel extract. Cells cultured with DMEM / F12 medium were set as the control group, and cells cultured with the extract of GPG hydrogel were set as the material control group. The specific experimental method is as follows: first, the material sample was irradiated under ultraviolet light for 48 hours to sterilize; then, the sample was placed in DMEM / F12 cell culture medium at a ratio of 0.1g / mL and extracted at 37°C for 24 hours to prepare the material extract; then, the extract was filtered using a 0.22μm bacterial sieve for further sterilization; finally, 10% fetal bovine serum was added to the sterilized extract. At the same time, the control group directly used DMEM / F12 with 10% fetal bovine serum to culture cells. After the cells were rinsed with PBS and digested with trypsin, they were seeded in a 96-well plate at a cell density of 5000 / well. Use DMEM / F12 medium to culture for 24 hours to ensure cell adhesion, and then replace the cell culture medium with the material extract. After 1 or 3 days of culture, discard the material extract and rinse the cells lightly with PBS 1 to 2 times, add 100 μL of CCK-8 reaction solution, and place it in a 37°C carbon dioxide cell culture incubator incubated in the dark for 2 hours. Finally, transfer the incubated CCK-8 reaction solution to a new 96-well plate, and measure the absorbance (OD) of each group of reaction solutions at a wavelength of 450nm by an enzyme-linked immunosorbent assay. Each group of samples is repeated three times.

[0114] 2. Live / Dead coloring

[0115] This study used the Live / Dead kit (Biyuntian). After the hydrogel extract was co-cultured with NPCs for 24 hours, the AM and PI dye solutions were mixed in equal amounts according to the instructions of the kit, diluted at a ratio of 1:1000, 500 μL of dye was added, incubated at 37°C for 10 minutes, and the cells were gently washed with PBS. The cells were then incubated with the working solution at room temperature for 30±45 minutes. After incubation, the working solution was removed, 10 μL of PBS was added, and the cells were observed under a fluorescence microscope.

[0116] 3. Lipid Peroxide (LPO) Staining

[0117] Prepare hydrogel extract. According to the instructions of the kit, cells were inoculated in 6 empty plates at a density of 2×105 / well. DMEM / F12 medium was used for 24 hours to ensure cell adhesion. A positive control group (normal cells treated with drugs), a control group (normal cells only, loaded with probes), and an experimental group (cells loaded with probes and treated with drugs) were set up. Reagent 2 was diluted 1:1000. 500μL of reagent 1 working solution was added to the blank group. The control group and the experimental group added an equal amount of reagent 2, incubated in a dark environment for 40 minutes, and washed the cells 2 to 3 times with reagent 1 working solution to fully remove the probes that did not enter the cells. The blank group and the control group added reagent 1 working solution, and the experimental group added hydrogel extract, incubated in a dark environment for 40 minutes, and washed the cells 2 to 3 times with reagent 1 working solution to fully remove the excess drugs in the experimental group. The experimental results were observed using a fluorescence microscope.

[0118] 4. Reactive oxygen species (ROS) staining

[0119] According to the previous culture method, 100 μm H 2 O 2 After 24 h of intervention, the cells were tested using a ROS detection kit (Biyuntian) and observed using a fluorescence microscope.

[0120] 5. Immunofluorescence Staining

[0121] The culture method was described above using 100 μM HO 2 O 2 Intervention of nucleus pulposus cells, after fixation, permeation, and blocking, incubated with the primary antibody MMP13 overnight, washed and then incubated with the secondary antibody at room temperature for 2 hours, washed and stained with DAPI at room temperature for 5 minutes, then washed away the residual reagents and observed with a confocal microscope. According to the above-mentioned culture method, 1μg / mL LPS was used to intervene in macrophages, fixed, permeated, and blocked, and incubated with the primary antibody IL-10 and TNF-a overnight, washed and then incubated with the secondary antibody at room temperature for 2 hours, washed and stained with DAPI at room temperature for 5 minutes, then washed away the residual reagents and observed with a confocal microscope.

[0122] Under normal circumstances, it emits red fluorescence through light excitation, and as lipid peroxidation progresses, the fluorescence changes from red to green. By enhancing the intensity of green fluorescence, the formation of LPO can be detected with high sensitivity. Fig.15 The results showed that the green fluorescence of cells was weakened to a certain extent after treatment with GPG gel, and the effect of weakening green fluorescence was more obvious after treatment with GPG9-NG1 gel, indicating that GPG9-NG1 gel can inhibit lipid peroxidation to a certain extent. Fig.16For the quantitative detection of LPO, the fluorescence intensity of the GPG9-NG1 group was significantly different from that of the control group, indicating that GPG9-NG1 inhibited lipid peroxidation. Fig.17 The cell viability of GPG9-NG1 gel extract was evaluated using the most commonly used CCK-8 test method to verify its cytotoxicity. After the material extract was incubated with the nucleus pulposus for 1 day and 3 days, the cytotoxicity of the material was observed. Fig.17 As shown in Figure 2, the cell viability of the GPG9-NG1 group was above 85% of the international standard, and the gel was considered to be non-cytotoxic. In addition, Live / Dead staining was used to verify their biosafety. The results are shown in Figure 2. Fig.18 As shown, it can be seen that all test groups have only a few dead cells marked with red fluorescent light, that is, during the culture process, the material has no effect on the normal growth of cells. In general, it is confirmed that GPG9-NG1 gel has good biocompatibility. Because the inner part of the intervertebral disc is in an ischemic and hypoxic microenvironment for a long time, the dynamic balance of the production and removal of reactive oxygen species is broken, causing a large amount of reactive oxygen species to accumulate inside the intervertebral disc. The accumulation of these products also activates the downstream inflammatory pathway, leading to the release of a large number of inflammatory factors inside the intervertebral disc.

[0123] Hydrogen peroxide, the most representative ROS, was selected to simulate the oxidative stress environment inside the intervertebral disc, and the material's resistance to oxidative stress of nucleus pulposus cells was demonstrated by staining. Fig.19 Zhong a Jing H 2 O 2 After treatment, the green fluorescence in the cells increased, while after culture with the hydrogel material, the ROS level decreased. In the intervertebral disc tissue, matrix metalloproteinase 13 (MMP13) can specifically degrade type II collagen (COL-II), the main component of the intervertebral disc ECM, and the imbalance between the production and degradation of ECM is the main cause of intervertebral disc degeneration. Therefore, blocking the oxidative stress process through biomaterials, further inhibiting the activation of acid-sensitive channels and the occurrence of downstream inflammatory cascade reactions, and promoting the reconstruction of the extracellular matrix are important treatment options for IVD. Immunofluorescence staining proved that GPG-NG hydrogel reduced the expression of MMP-13 ( Fig.19 (b) Through immunofluorescence staining of macrophages, the effect of the material on inflammation was further explored. It can be seen that the GPG-NG group gel reduced the expression of the pro-inflammatory factor TNF-a, promoted the expression of the anti-inflammatory factor IL-10, and helped to improve the inflammatory environment.

[0124] Fig. 20 The composite hydrogel (GPG) in Comparative Example 1 and the animal glue composite hydrogel (GPG-NG) in Example 2 were subjected to macrophage IL-10 immunofluorescence staining under LPS stimulation; Fig.21This is the immunofluorescence staining of TNF-a in macrophages of the composite hydrogel (GPG) in Comparative Example 1 and the animal glue composite hydrogel (GPG-NG) in Example 2 under LPS stimulation.

[0125] from Fig. 20 It can be seen that after LPS stimulation, the cell fluorescence was weaker than that of normal cells, the fluorescence intensity of the GPG group and GPG-NG group was stronger than that of the LPS group, and the GPG-NG group was better than the GPG group, that is, GPG-NG promoted the expression of the anti-inflammatory factor IL-10.

[0126] from Fig.21 It can be seen that after LPS stimulation, the cell fluorescence is enhanced compared with normal cells. The fluorescence intensity of the GPG group and GPG-NG group is weaker than that of the LPS group, while that of the GPG-NG group is lower than that of the GPG group, that is, GPG-NG reduces the expression of the pro-inflammatory factor TNF-a.

[0127] (11) Evaluation of hydrogel effects in vivo

[0128] 1) Toxicological evaluation

[0129] A rat coccygeal disc degeneration model was established. Twelve male SD rats (eight weeks old) were used in this study. After the rats were anesthetized and disinfected with ethanol, a longitudinal incision of about 3 to 4 cm was made along the central dorsal side of the mouse tail corresponding to the skin of the C3 to C8 intervertebral discs. The tail muscles and ligaments were bluntly separated to expose the intervertebral disc. The NP tissue was extracted and removed using a syringe. Before the NP tissue inside the intervertebral disc was completely extracted, the viscous gel-like NP tissue blocked the needle, creating obvious resistance when the syringe was withdrawn. The moment the NP tissue was sucked in, the resistance to withdrawal disappeared, which was used as a sign of NP removal. After removing the NP, the hydrogel was injected into the intervertebral disc after NP discectomy, the wound was sutured, and the rats were disinfected with ethanol. 1 / 2 of the rats were collected at 4 and 8 weeks after surgery, and the heart, liver, spleen, lung, and kidney tissues of the modeled rats were taken and made into pathological sections. Fig. 22 These are pathological sections of rats (after material implantation), where (a) is four weeks and (b) is eight weeks.

[0130] like Fig. 22 As shown in a and b, the results of tissue pathology sections indicate that the material is non-toxic and there are no lesions in the heart, liver, spleen, lung, and kidney of the rats.

[0131] 2) Rat intervertebral disc imaging and histological staining evaluation

[0132] MRI test: 8 weeks after puncture modeling, SD rats were subjected to MRI sagittal SE sequence T2WI scanning, and the scanning parameters were set as follows: TR = 3000mS, TE = 80mS, FOV = 200mm×200mm, Thick = 1.4mm. The degree of intervertebral disc degeneration was evaluated by comparing the changes in T2WI signal strength of the intervertebral discs in different groups.

[0133] Tissue section staining was as follows: 8 weeks after puncture modeling, SD rats were over-anesthetized and killed. The rat tail was transected with a sterile surgical blade to remove the epidermis and excess vertebral segments, retaining the complete intervertebral disc structure, adjacent vertebral bodies and muscle ligament tissues of the normal group, GPG group, GPG-NG group and acupuncture group. The rat spinal specimens were fixed with 4% paraformaldehyde for 48 hours, and then washed and decalcified with 15% ethylenediaminetetraacetic acid (EDTA): pH = 7.4, for about 4 weeks. The decalcified samples were embedded in paraffin. 7μm midsagittal sections were taken for histological staining.

[0134] Fig.23 MRI images of rats 8 weeks after surgery (a) and H&E staining and Safranin-O / fast green staining images of the coccygeal intervertebral discs of rats in various treatment groups at 8 weeks, respectively (b), where the upper image is the H&E staining image and the lower image is the Safranin-O / fast green staining image.

[0135] MRI observation results showed that ( Fig.23 (a) After 8 weeks, the signal expression intensity and range of the nucleus pulposus tissue in the puncture group were further weakened, which was different from the normal group; the signal expression intensity and range of the nucleus pulposus tissue in the GPG group were weakened, which was different from the normal group; the signal expression intensity and range of the nucleus pulposus tissue in the GPG-NG group changed less and were close to the normal group, which was different from the puncture group. In order to further evaluate the effect of different organic hydrogel scaffolds in the treatment of intervertebral disc degeneration, the histological morphology of the intervertebral disc was observed by H&E staining, and the content and distribution of type II collagen were characterized by safranin-O / fast green staining ( Fig.23 (b) The results showed that the normal group showed a complete intervertebral disc physiological structure after 8 weeks, with an oval nucleus pulposus and rich in type II collagen. After 8 weeks, the nucleus pulposus tissue in the puncture group almost disappeared and no type II collagen was expressed, and the annulus fibrosus structure was severely distorted. After 8 weeks of GPG implantation, the nucleus pulposus tissue in the GPG group was damaged, and the expression of type II collagen was low. After 8 weeks of GPG-NG implantation, a large number of nucleus pulposus cells and extracellular matrix were visible in the GPG-NG group, and the expression of type II collagen was high and evenly distributed in the nucleus pulposus tissue. The annulus fibrosus structure only changed slightly and still showed an orderly thin layer of annular stacking structure.

[0136] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An animal glue composite hydrogel, characterized in that: include: Animal glue, polyvinyl alcohol, glycerol and water; the mass ratio of the animal glue, polyvinyl alcohol, glycerol and water is 0.1-1.5:0.1-0.3:3-8:2-8.

2. The animal glue composite hydrogel according to claim 1, characterized in that: The animal glue is animal-derived gelatin; the animal-derived gelatin includes one or more of fish bladder glue, fish skin glue, cowhide glue and donkey skin glue; the weight average molecular weight of the polyvinyl alcohol is 1500-220000.

3. The method for preparing the animal glue composite hydrogel according to claim 1 or 2, characterized in that: The method comprises the following steps: mixing an aqueous solution of animal glue, an aqueous solution of polyvinyl alcohol and glycerol, and allowing the obtained viscous solution to stand and solidify to obtain the animal glue composite hydrogel.

4. The preparation method according to claim 3, characterized in that: The mass concentration of the animal glue in the aqueous solution of the animal glue is 15-40%.

5. The preparation method according to claim 3, characterized in that: The mass concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 5-15%.

6. The preparation method according to claim 3, characterized in that: The mixing temperature is 45-65°C.

7. The preparation method according to claim 6, characterized in that: The mixing is carried out under stirring conditions; the stirring rate is 10 to 500 rpm.

8. The preparation method according to claim 3, characterized in that: The static curing time is 3 to 6 hours; the static curing is carried out at room temperature; the room temperature is 15 to 42°C.

9. The preparation method according to claim 3, characterized in that: The preparation method of the aqueous solution of animal glue comprises the following steps: soaking the animal glue in water, dissolving it in a water bath and eliminating bubbles in sequence to obtain the aqueous solution of the animal glue; the soaking time is 12 to 24 hours; the temperature of the water bath dissolution is 45 to 65°C.

10. Use of the animal glue composite hydrogel according to claim 1 or 2 or the animal glue composite hydrogel prepared by the preparation method according to any one of claims 3 to 9 in the preparation of nucleus pulposus repair preparations.

Citation Information

Cited By

  • Natural protein-based multifunctional biogel as well as preparation method and application thereof

    CN121021864A

  • Dithioformate-metal coordination two-dimensional network material, composite hydrogel and application thereof

    CN121086263A

  • Dithioformate-metal coordination two-dimensional network material, composite hydrogel and application thereof

    CN121086263B